Comparison of the performance of three PCR assays for the detection and differentiation of Theileria orientalis genotypes - Perera, Piyumali K (Parasit Vectors, 2015)
BACKGROUND: Oriental theileriosis is a tick-borne disease of bovines caused by the members of the Theileria orientalis complex. Recently, we developed a multiplexed tandem (MT) PCR to detect, differentiate and quantitate four genotypes (i.e., buffeli, chitose, ikeda and type 5) of T. orientalis. In this study, we used MT PCR to assess the prevalence and infection intensity of four T. orientalis genotypes in selected cattle herds that experienced oriental theileriosis outbreaks in New Zealand, and compared the sensitivities and specificities of MT PCR, PCR-high resolution melting (PCR-HRM) and a TaqMan® qPCR. METHODS: MT PCR, PCR-HRM analysis for T. orientalis and a TaqMan® qPCR assay for ikeda genotype were employed to test 154 and 88 cattle blood samples from North (where oriental theileriosis outbreaks had occurred; designated as Group 1) and South (where no outbreaks had been reported; Group 2) Islands of New Zealand, respectively. Quantitative data from MT PCR assay were analyzed using generalized linear model and paired-sample t-test. The diagnostic specificity and sensitivity of the assays were estimated using a Bayesian latent class modeling approach. RESULTS: In Group 1, 99.4% (153/154) of cattle were test-positive for T. orientalis in both the MT PCR and PCR-HRM assays. The apparent prevalences of genotype ikeda in Group 1 were 87.6% (134/153) and 87.7% (135/154) using the MT PCR and Ikeda TaqMan® qPCR assays, respectively. Using the MT PCR test, all four genotypes of T. orientalis were detected. The infection intensity estimated for genotype ikeda was significantly higher (P = 0.009) in severely anaemic cattle than in those without anaemia, and this intensity was significantly higher than that of buffeli (P < 0.001) in the former cattle. Bayesian latent class analysis showed that the diagnostic sensitivities (97.1-98.9%) and specificities (96.5-98.9%) of the three PCR assays were very comparable. CONCLUSION: The present findings show the advantages of using the MT PCR assay as a useful tool for in-depth epidemiological and transmission studies of T. orientalis worldwide.